Pendampingan Mahasiswa KPM untuk Sinergitas Muhamadiyah dan Nahdlatul Ulama di Desa Sahang: untuk Menguatkan Peran Keumatan dan Kebangsaan - Muhammad Ibnu Soleh; Tamrin Fathoni (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article aims to describe the synergy between Muhammadiyah and Nahdlatul Ulama (NU) in Sahang Village, Ngebel District, Ponorogo Regency, as an effort to strengthen religious service and nationalism. The Audience (A) of this study is the community of Sahang Village, particularly members of Muhammadiyah and NU. The Behavior (B) expected is the establishment of collaboration in education, social, economic, and youth activities. The Condition (C) of this research is implemented through the Community Service Program (KPM) using a descriptive qualitative approach with observation, interviews, and documentation methods. The Degree (D) shows that the synergy between Muhammadiyah and NU can strengthen ukhuwah wathaniyah (national unity), reduce potential social segregation, and increase youth participation in religious and national activities. Thus, the collaboration of these two organizations becomes an important strategy in building social harmony and reinforcing national values at the village level.